Evaluation of Inappropriate Medication Use and Compliance in Elderly People - Yilmaz, Fikriye; Colak, Meric Y. (Current Drug Safety, 2018)
Objective: The aim of this study is to evaluate the potentially inappropriate medication use and medication compliance in elderly patients who buy prescribed drugs from a pharmacy in Ankara. Methods: In this cross-sectional field study, 200 older people who bought prescribed drugs from a pharmacy which is close to several hospitals in Ankara in April 2016 were chosen as random sample. A questionnaire consisting of questions related to socio-demographic characteristics, health status, drug use of elderly and Morisky Green Levine Medication Adherence Scale (MGLS) was used to collect data. The appropriateness of the drugs prescribed for elderly was determined by the pharmacist according to Beers criteria. The data were evaluated by descriptive statistics and Chi-Square test. Results: 57.4% of the 200 elderly patients in the study are women and the mean age is 72.55 ± 6.34 years; 72.6% of them are below high school. When the medication compliance was examined, 36.3% of them did not comply with the drug treatment according to MGLS. It was determined that having sufficient information about the drug, education level, occupation and polymorbidity affect medication adherence (p <0.05). When the appropriateness evaluated according to Beers Criteria, 41.7% of the subjects were prescribed potentially inappropriate medications (PIM). According to the analysis, the number of drugs prescribed and the type of the chronic disease have effects on the inappropriate prescription (p <0.05). Conclusion: According to the study, the prevalence of inappropriate medication use in the elderly is higher than the medication non-adherence.
Keywords: MGLS